Evolution of economic sustainability terminology in EU legislation: a descriptive and quantitative perspective - Jaspe Nieto, Javier; Ortega Larrea, Ana Lucia; Bordonado Bermejo, Maria Julia (Transformations In Business & Economics, 2025)
Within the realm of governmental activity, the alignment of verbal expressions with diverse theoretical or ideological frameworks gives rise to distinct manifestations of the „social construction of reality “within public opinion. This study aims to scrutinize the discourse characteristics employed by the legislative superstructure of the European Union (EU). Rather than seeking causal explanations based on hypotheses, the research confines itself to elucidating the phenomenon as it exists, deducing its constituent elements deductively from a pre-established conceptual framework. To achieve this, the widely utilized ATLAS.ti tool for applied semantic studies is employed. Discourse trends appear to revolve around the social impact of development economics, the pivotal role assigned to future generations, the significance of target-oriented plans and programs, and the equilibrium among social, environmental, and economic dimensions. The temporal constraints warrant a more extensive investigation into the evolution of the EU's legislative discourses that contribute to the construction of reality.